Beating Goliath : Why Insurgencies Win - Record, Jeffrey (Book collections on Project MUSE., 2007)
"Beating Goliath examines the phenomenon of victories by the weak over the strong - more specifically, insurgencies that succeeded against great powers. Jeffrey Record reviews eleven insurgent wars from 1775 to the present and determines why the seemingly weaker side won. He concludes that external assistance correlates more consistently with insurgent success than any other explanation. He does not disparage the critical importance of will, strategy, and strong-side regime type or suggest that external assistance guarantees success. Indeed, in all cases, some combination of these factors is usually present. But Record finds few if any cases of unassisted insurgent victories except against the most decrepit regimes." "Having identified the ingredients of insurgent success, Record examines the present insurgency in Iraq and whether the United States can win. In so doing, Record employs a comparative analysis of the Vietnam War and the Iraq War. He also identifies and assesses the influence of distinctive features of the American way of war on the U.S. forces performance against the Iraqi insurgency."--Jacket